COMPARATIVE ANALYSIS OF CSR ACTIVITIES OF FORBES GLOBAL FIRMS DURING COVID-19 AND PRE COVID-19 USING SOCIAL MEDIA ANALYTICS - Thakur, Shivani; Kumar, Manoj (The journal of contemporary issues in business and government, 2022)
This research looked into how the Covid-19 pandemic might affect the company’s CSR efforts. According to the analysis, the COVID-19 pandemic provides a great chance for corporations to adopt genuine and meaningful CSR practises. In this study, top 100 Forbes global Firms' Twitter data was extracted from their Twitter profiles, and topic modelling was performed to identify CSR activities carried out by the firm during the COVID 19 pandemic. Using social media data, this study compared the firm's CSR activities during the COVID 19 and pre-COVID 19 periods. The findings revealed that this pandemic presents great opportunities for organizations to actively participate in various CSR programs during the crisis, possibly initiating a new era of CSR advancement. Fortunately, the study found that many companies have not only overlooked socially responsible business practises during this crisis, but have also actively participated in various socially responsible activities, especially those that can provide prompt help and support in the virus's fight. This paper presents some exploratory thoughts on how the pandemic might affect CSR performance of the Forbes global firms. In terms of CSR, the study discussed about how it affects CSR opportunities and patterns.